2020
DOI: 10.4040/jkan.2020.50.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effect of a Smartphone Overdependence Prevention Program for University Students Based on Self-Determination Theory

Abstract: This study aimed to develop a smartphone overdependence prevention program for college students based on the self-determination theory (SDT) and evaluate its effectiveness. Methods: A non-equivalent control group repeated measures design was used for the study. Participants were 64 university freshmen (experimental group: 29, control group: 35). The developed program consists of eight sessions conducted twice a week. The program was designed to promote autonomy, competence, and relatedness the three elements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In the present study, the self-regulatory ability showed an increase during the follow-up period in EG1 and EG2 although such increase was statistically insignificant. This result was similar to results of a previous study on smartphone overdependence among college students [20]. We speculate that with the support of peers, participants could recognize their problematic behavior regarding smartphone use.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, the self-regulatory ability showed an increase during the follow-up period in EG1 and EG2 although such increase was statistically insignificant. This result was similar to results of a previous study on smartphone overdependence among college students [20]. We speculate that with the support of peers, participants could recognize their problematic behavior regarding smartphone use.…”
Section: Discussionsupporting
confidence: 90%
“…The sense of belonging formed through group activities with common interests at the beginning of the semester can have a positive effect on improving relatedness [8,15]. Considering that participants of this program were college freshmen, positive relationships built by the program and group efforts to control smartphone use might have contributed to enhanced relatedness [20]. Since intimate relationships have a positive effect on the control of smartphone use [25], social support is needed to maintain relationships formed through the program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations